ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI BILANGAN BULAT DITINJAU DARI ADVERSITY QUOTIENT - Muhtarom Muhtarom; Elly Putri Sholihah; Sutrisno Sutrisno (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to describe the stages of student problem solving based on the Polya stages in terms of adversity quotient on integer material. Based on these objectives, this research is descriptive qualitative research. The data were collected from grade VII students at SMP Negeri 1 Karanganom who were selected by purposive sampling. The subjects selected in this study were 3 students, consisting of 1 student who was type AQ quitter, 1 student who was type AQ campers, and 1 student who typed AQ climbers. Data collection techniques used were AQ questionnaire, tests, interviews, and completed with documentation. The data analysis techniques used are data reduction, display data, and conclusion drawing/verification. The validity of the data used was technical triangulation. In this study, the QSR Nvivo software was used to help process and analyze research data. The results in this study indicate: 1) The quitters subject can understand the problem, is less able to prepare a resolution plan, is less able to solve problems according to the plan, and is less able to re-examine the results that have been obtained. 2) The campers subject can understand problems, able to plan resolution, able to solve problems, and less able to re-examine the results that have been obtained. 3) The climbers' subject was able to understand the problem, was able to plan the solution, was able to solve the problem according to the plan, and was able to re-examine the results that had been obtained